2022
DOI: 10.1007/s44202-022-00025-7
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style and its effect on eating disorders and substance abuse across the young population

Abstract: This article attempts to examine the occurrence of two behavioural changes, namely, substance abuse and eating disorders in order of onset mediated by ineffective parenting styles during young age. The four parenting styles and their consequential behavioural adverse effects are taken as the focal point of this study and are synthesized to provide an outlook on the status of ineffective parenting and deviant offspring behaviours. A review of literature was primarily undertaken to examine the characteristic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 120 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Maladaptive behaviors can be generated by individual intolerance to setbacks or difficulties, or sheer pessimism [63]. Recent studies have shown that parental rearing patterns not only can significantly affect adolescents' mental health [64], but also effect eating disorders and substance abuse [65]. Furthermore, students' goal orientation, personality traits and parental rearing patterns are also closely related [66].…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive behaviors can be generated by individual intolerance to setbacks or difficulties, or sheer pessimism [63]. Recent studies have shown that parental rearing patterns not only can significantly affect adolescents' mental health [64], but also effect eating disorders and substance abuse [65]. Furthermore, students' goal orientation, personality traits and parental rearing patterns are also closely related [66].…”
Section: Discussionmentioning
confidence: 99%
“…A typical example is, kids who grow up with permissive parents often don't know how to follow rules or control themselves, which can lead to drug abuse [16]. When parents are anxious, it can lead to anxious attachment styles in their children which can then lead to anxiety disorders and more often than not substance abuse disorders [16]. Parenting styles can influence abuse of substance [16].…”
Section: Compare and Contrast The Effects Of Different Parenting Styl...mentioning
confidence: 99%
“…When parents are anxious, it can lead to anxious attachment styles in their children which can then lead to anxiety disorders and more often than not substance abuse disorders [16]. Parenting styles can influence abuse of substance [16].…”
Section: Compare and Contrast The Effects Of Different Parenting Styl...mentioning
confidence: 99%
“…It sets into stone a behavioural health pattern that proves to be debilitating for the rest of their lives. One of the primary causal factors for substance use disorder has been impaired parenting and family functioning, which is the leading cause of ineffective parenting 2 . For instance, parental substance use is prospectively associated with a greater tendency of adolescent substance use, relatively high levels of conflict, anger, criticism, harsh parenting, and hostility, and lower levels of cohesion, support, and warmth; and problematic parenting styles, practices, and communication 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%